Bring life into law and bring law into life-story about making law and enforcing law in Viet Nam - Nguyen, Hoang Anh (Vietnam national university, Hanoi, 2020)
There are many reasons for the abundance of legal normative documents in Vietnam. As a country influenced by the Civil Law, the written laws are prefered. Going from a centrally planned economy, bureaucracy government intervenes in almost all areas of social life, and the consequence is the inflation of legal documents. Precedents have been officially recognized since 2015, which once again affirmed the nearly dominant position of the written law source. Although in recent years the law-making process has been standardized and enhanced the policy analysis and RIA (Regulatory Impact Assesement) in accordance with the model of the developed countries, but their application in the cultural, economic institution in Vietnam is still difficult. The consequences are very difficult to ―bring life into law. The law is abundant but their contents sometimes are not applicable for life; not encouraging development. Consequently, it is difficult to "bring law into life". In order to have good law enforcement not only need good legal documents. Promoting accountability and decentralization in the administrative system; strengthening the supervision of the courts in enforcing laws are the necessary solutions for better law enforcement. The following article discuss the difficulties and prospects in drafting and enforcing laws in Vietnam.